2022
DOI: 10.2340/17453674.2022.3512
|View full text |Cite
|
Sign up to set email alerts
|

Impact of patient and prosthesis characteristics on common reasons for total knee replacement revision: a registry study of 36,626 revision cases from Australia, Sweden, and USA

Abstract: Background and purpose: Total knee replacement (TKR) studies usually analyze all-cause revision when considering relationships with patient and prosthesis factors. We studied how these factors impact different revision diagnoses.Patients and methods: We used data from 2003 to 2019 of TKR for osteoarthritis from the arthroplasty registries of Sweden, Australia, and Kaiser Permanente, USA to study patient and prosthesis characteristics for specific revision diagnoses. There were 1,072,924 primary TKR included an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…It is one of Europe and North America’s most widely performed elective orthopedic procedures [ 1 , 2 ]. Despite an optimal implant survival of more than 90% after 15 years, according to long-term studies and registry data [ 3 , 4 ], one in five patients is dissatisfied with surgical treatment [ 5 , 6 ]. There may be multiple reasons behind these results.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of Europe and North America’s most widely performed elective orthopedic procedures [ 1 , 2 ]. Despite an optimal implant survival of more than 90% after 15 years, according to long-term studies and registry data [ 3 , 4 ], one in five patients is dissatisfied with surgical treatment [ 5 , 6 ]. There may be multiple reasons behind these results.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of previous studies reported preoperative and postoperative outcome scores for patients of TKR showed that the procedure was effective [20]. The mentioned studies included patients of various ages and used a variety of prostheses and techniques to implant the device [21,22]. TKR was effective in all of the studies [21][22].…”
Section: -Removing Gapsmentioning
confidence: 99%
“…The mentioned studies included patients of various ages and used a variety of prostheses and techniques to implant the device [21,22]. TKR was effective in all of the studies [21][22]. Furthermore, unicompartmental knee replacement (UKR) surgery seems to be as effective as TKR surgery for people who have the indications for it.…”
Section: -Removing Gapsmentioning
confidence: 99%
“…Artificial joint implants can be fixed with cement to bind the bone to the implant through mechanical interlocking, or alternatively cementless surgery is applied expecting implants to generate bone at the implant surface to stabilize the implant. A randomized controlled trials and the registry studies indicated that cemented implants reduce postoperative pain and provide better joint function than cementless implants, thus improving the quality of life for the patients in the areas of hip, knee, and shoulder joints [ 1 , 2 , 3 , 4 , 5 ]. However, the use of bone cement carries a risk of adverse events, with hypotension and shock widely reported in the literature [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%